Impact of visceral adipose tissue on the accuracy of T-staging by CT in colon cancer. Issue 134 (January 2021) - Liu, Li-Heng; Zhou, Guo-Feng; Zhou, Jian-Jun; Rao, Sheng-Xiang; Zeng, Meng-Su
Abstract: Objective: Accuracy of preoperative T-staging for colon cancer remains disappointing and may potentially influenced by patients' individual characteristics including visceral adipose tissue (VAT). We sought to clarify the impact of VAT on the accuracy of T-staging by CT. Methods: This study of 216 consecutive patients who underwent elective surgery was conducted in a single cancer center, to control other potentially confounding factors. Patients were divided into accurate- and mis-staging groups according to the comparison between preoperative CT-defined (cT) and postoperative pathologic T-stages (pT). Patients' individual characteristics, including CT-based VAT at L2/L3 level, age, sex, body mass index (BMI), tumor location, present of bowel obstruction and pathologic subtype, were compared between the two groups. Association between VAT and mis-staging was assessed using multivariate logistic regression to adjust for confounders. Results: Of the 216 patients, 84 (39%) were mis-staged by CT. The mean VAT in accurate-staging group was significantly higher than that in mis-staging group (146.8 ± 66.1 cm 2 vs 98.1 ± 44.7 cm 2, P < 0.001), with an optimal cutoff point of 122 cm 2 for predicting mis-staging. After partial adjustment, a lower VAT (< 122 cm 2, P < 0.001) and proximal location of tumor (P = 0.004) were independent factors associated with higher probability of mis-staging. Compared to VAT ≥ 122 cm 2 as the reference, VAT < 122 cm 2 exhibited an odds ratio of 2.701 (95% confidence intervals [CI], 1.618-3.907) for the probability of mis-staging. Conclusion: A lower-VAT is associated with an increased probability of inaccurate clinical T-staging in colon cancer.